Mediastinal effusion due to pericardiocentesis with cardiac tamponade: a case report - Zhang, Qian (BMC Anesthesiol, 2021)
BACKGROUND: Pericardiocentesis is an effective treatment for cardiac tamponade, but there are risks, including haemorrhagic events, cardiac perforation, pneumothorax, arrhythmia, acute pulmonary oedema and so on. Mediastinal effusion caused by puncture is rarely reported. CASE PRESENTATION: A 47-year-old man who had a history of right leg deep vein thrombosis and pulmonary artery embolism with implantation of an inferior vena cava filter presented for inferior vena cava filter removal. Within 30 min after the procedure, he developed chest pain, nausea, vomiting and presyncope with shock. Echocardiography confirmed massive pericardial effusion with evidence of cardiac tamponade. Emergency pericardiocentesis was performed. Confusingly, only 3 mL of bloody pericardial effusion was drained in total, and subsequently, the patient’s symptoms rapidly improved with stable haemodynamics. Repeat echocardiography showed that the pericardial effusion had disappeared. Urgent computed tomography pulmonary angiography demonstrated localized effusion, which was not seen the previous computed tomography results and was noted around the left ventricle in the mediastinal apace. No intervention was performed, given that there was no bleeding tendency or further adverse events related to the mediastinal effusion. The patient was subsequently discharged in a stable condition a few days later, and outpatient follow-up was advised. CONCLUSIONS: Mediastinal effusion is a rare complication of pericardiocentesis. In the case described herein, the most likely cause was pericardial effusion extravasated into the mediastinum through the needle insertion site in the puncture process due to large pressure variations in the intrapericardial space with tamponade, differing from cases of over-anticoagulation reported in the previous literature. Just as our case demonstrates that conservative treatment of an hemodynamic insignificant mediastinal effusion may be appropriate. Echocardiography is useful and effective to minimize complication rates. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12871-021-01385-8.